Pemanfaatan Fly Ash sebagai Adsorben dalam Pemurnian Crude Glycerol dari Hasil Produk Samping Biodiesel - Riza Alviany; Dhea Novita; Rizky Anggara Pratama; Fadhil Muhammad Tarmidzi (Jurnal Serambi Engineering, 2023)
The increase of biodiesel production capacity is followed by an increase in crude glycerol production as a by-product. Crude glycerol still has a low purity and a lot of impurities so it requires special treatment so that it can be utilized and valuable. One of the ways to increase the purity of crude glycerol is in the adsorption process. This study aims to determine the best conditions for the adsorption process and the characteristics of the glycerol produced after the adsorption process. The initial condition of crude glycerol purity is low, namely 67.8%, so purification is needed. One way of purifying crude glycerol is by physically separating it using fly ash as an adsorbent. The experiment was carried out with the adsorption process using fly ash with the adsorbent mass variable 30,35,40,45, and 50 grams and the adsorption time variable was 50,60, and 70 minutes. The purified products are analyzed quantitatively and qualitatively, including glycerol content, density, viscosity, moisture content, ash, and MONG. The best conditions for the adsorption process using fly ash were obtained at a mass of 50 grams with a time of 50 minutes with the results that the glycerol content was 97.5%, water content 0.03%, ash content 0.0432%, MONG content 2.426%, density 1.253 gr / ml , viscosity 233.56 cP. Based on these results, purified glycerol was obtained that met the quality standards of SNI 06-1564-1995.